Pengaruh Intellectual Capital, Inventory Turnover dan Profitabilitas Terhadap Financial Distress - Riyana Eka Sapitri; Dirvi Surya Abbas; Sriyanto, Sriyanto (Universitas Katolik Widya Karya Malang, 2024)
The purpose of this study was to determine the effect of intellectual capital, inventory turnover and profitability on financial distress in mining sector companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 5 years, namely the period 2017 - 2021. The population of this study includes all mining sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2017 - 2021. The sampling technique in the study used purposive sampling technique. Based on the predetermined criteria, 13 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data logistic regression analysis. The results showed that intellectual capital and inventory turnover had no effect on financial distress. While profitability has a significant negative effect on financial distress, and intellectual capital, inventory turnover and profitability jointly affect financial distress.